2022
DOI: 10.1136/bmjgh-2021-007190
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 pandemic lockdown on movement behaviours of children and adolescents: a systematic review

Abstract: IntroductionSeveral studies have examined how the lockdown restrictions enforced to halt the spread of COVID-19 have affected children and adolescents’ movement behaviours, but there is a need to synthesise these findings. Therefore, we conducted this systematic review to examine the impact of COVID-19 lockdown on children and adolescents’ movement behaviours.MethodsWe searched eight databases and grey literature for relevant studies of all study designs; and conducted a narrative analysis of the results follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
86
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(119 citation statements)
references
References 97 publications
11
86
3
Order By: Relevance
“…In this study, there was no significant change in sleep duration; however, most of the children had their bedtime and waketime shifted to later because of the quarantine. A recent systematic review that combined 71 studies from 35 different countries to explore the impact of the restrictions among children and adolescents reported discrepancies on the effect of the pandemic on sleep ( 49 ). Nevertheless, our findings correlated with 11 studies that showed no significant change in sleep duration, and 10 other studies that reported a shift to a later bedtime and wake time ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, there was no significant change in sleep duration; however, most of the children had their bedtime and waketime shifted to later because of the quarantine. A recent systematic review that combined 71 studies from 35 different countries to explore the impact of the restrictions among children and adolescents reported discrepancies on the effect of the pandemic on sleep ( 49 ). Nevertheless, our findings correlated with 11 studies that showed no significant change in sleep duration, and 10 other studies that reported a shift to a later bedtime and wake time ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review that combined 71 studies from 35 different countries to explore the impact of the restrictions among children and adolescents reported discrepancies on the effect of the pandemic on sleep ( 49 ). Nevertheless, our findings correlated with 11 studies that showed no significant change in sleep duration, and 10 other studies that reported a shift to a later bedtime and wake time ( 49 ). Clearly, the stresses brought by the pandemic encouraged a shift toward an evening oriented circadian rhythm.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Nevertheless, lockdowns, supply chain complications, and isolation have had an impact on children. School closures and regional lockdowns were detrimental to children and adolescents' physical activity owing to more time on screen and longer periods of sleep, 5 and increases in housing and food insecurity were well documented, with concerns about the long-term health of children. 6 Furthermore, reliable reports in the early stages of the pandemic described an increased prevalence of depression, anxiety, and behaviour problems in children, 7 as well as delays in seeking emergency care.…”
mentioning
confidence: 99%
“…The COVID‐19 pandemic has had adverse effects on the well‐being, health and behaviour of children and adolescents, probably due to social restrictions. 1 , 2 , 3 A lot of studies were conducted during the particularly challenging first year of the pandemic, when there were lockdowns and day care, schools and leisure facilities were closed. Our online survey in February 2022 investigated parents' perceptions of the long‐term consequences of the pandemic on child development.…”
mentioning
confidence: 99%
“…Changes to health, well‐being, friendships, learning ability and school performance were more frequently perceived as negative than positive, in line with previous studies. 1 , 3 Possible explanations include reduced contact with peers, 1 lack of exercise during restrictions 2 and limited support during distance learning. 3 Changes in family relationships and autonomy were more frequently perceived as positive than negative, probably because school closures triggered more time alone and more time with families.…”
mentioning
confidence: 99%